Illegal Ministerial Circulars in Indonesia: Implications for Legitimacy: Surat Edaran Menteri yang Tidak Sah di Indonesia: Implikasi bagi Legitimasi - Gunawan, Ari; Susetio, Wasis; Markoni, Markoni; Subiyanto, Achmad Edi (Universitas Muhammadiyah Sidoarjo, 2023)
This normative research aimed to examine the extent of ministerial circular letters in Indonesia and whether a particular circular letter violates the Law Number 17 of 2014. Through a qualitative literature review and legal analysis, the study found that Minister of Finance Circular Letter Number S-841/Mk.02/2014 does not fall under the category of legislative rules and lacks external application, thus rendering it illegal. The study suggests that ministerial circular letters must adhere to the law, philosophy, and social considerations to be considered legitimate. The findings have implications for the proper implementation and interpretation of ministerial circular letters in Indonesia. Highlights: Ministerial circular letters in Indonesia must comply with the law, philosophical principles, and social considerations to be considered legitimate. Ministerial circular letters are not regulations that apply to the general public, but only to ministries or institutions. Ministerial circular letters that contradict higher laws are considered illegal.